2005
DOI: 10.1071/fp04003
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defences in olive trees during drought stress: changes in activity of some antioxidant enzymes

Abstract: The effects of drought on the activities of superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), guaiacol peroxidase (POD), indoleacetate oxidase (IAAox) and polyphenol oxidase (PPO) were studied in 2-year old Olea europaea L. (cv. ‘Coratina’) plants grown under high temperatures and irradiance levels and gradually subjected to a controlled water deficit. After 20 d without irrigation, mean predawn leaf water potential fell from –0.37 to –5.37 MPa, and decreases in net photosynthesis and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
84
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(106 citation statements)
references
References 40 publications
16
84
1
5
Order By: Relevance
“…On the other hand, the DENTAMET ® -treated infected plants were characterized by a higher sugar content. In this case, the observed polyphenols decrease, in treated with respect to control trees, is in accord with the polyphenols production associated to drought stress [24,25], notwithstanding the levels of phenols are characteristic for each cultivar such as abiotic stress responses [26][27][28]. Interestingly, when unsupervised exploratory method (PCA) was applied a good grouping according to the original cultivar (Ogliarola salentina and Cellina di Nardò) resulted only in the case of DENTAMET ® -treated samples while the differences normally observed according to the olive cultivars were not predominant in the case of untreated CoDiRO-exhibiting plants.…”
Section: Showing a Clear Partition Between Dentametsupporting
confidence: 60%
See 1 more Smart Citation
“…On the other hand, the DENTAMET ® -treated infected plants were characterized by a higher sugar content. In this case, the observed polyphenols decrease, in treated with respect to control trees, is in accord with the polyphenols production associated to drought stress [24,25], notwithstanding the levels of phenols are characteristic for each cultivar such as abiotic stress responses [26][27][28]. Interestingly, when unsupervised exploratory method (PCA) was applied a good grouping according to the original cultivar (Ogliarola salentina and Cellina di Nardò) resulted only in the case of DENTAMET ® -treated samples while the differences normally observed according to the olive cultivars were not predominant in the case of untreated CoDiRO-exhibiting plants.…”
Section: Showing a Clear Partition Between Dentametsupporting
confidence: 60%
“…In contrast, in the case of Ogliarola salentina CoDiRO-exhibiting trees, DENTAMET ® -untreated samples showed a higher content of polyphenol molecules while samples from treated infected plants were characterized by a higher sugar content. As already reported in literature [24,25], physiological and biochemical responses to stress are closely cultivar-dependent. In the present case, since studied Ogliarola salentina and Cellina di Nardò cultivar trees were also characterized by a different level of pathogen attack, the observed changes in metabolic profiles due to DENTAMET ® treatment could be also related to such a specific factor.…”
Section: Showing a Clear Partition Between Dentametmentioning
confidence: 52%
“…Agüero et al (2008) however, have shown that neither absolute water content or relative water content (relative to the total water holding capacity of the tissue) are significantly correlated with variation in overall lettuce quality (which includes a measure of discolouration). Water-deficit stress has also been shown to increase the concentration of certain phenolic compounds in lettuce, particularly chicoric acid (Oh et al 2010) and to cause the accumulation of antioxidant compounds (Sofo et al 2005;Oh et al 2010), which may potentially inhibit oxidation of phenolics and thus discolouration development. Whilst there is no evidence to specifically associate increased levels of chicoric acid with a reduction in the level of lettuce discolouration, the different pathways involved in phenylpropanoid metabolism are interlinked (Treutter 2010), consequently, the diversion of plant resources into one pathway (i.e.…”
Section: Watermentioning
confidence: 99%
“…Enhanced antioxidant levels are associated with increased tolerance to drought induced oxidative stress in Olea europea (Sofo et al, 2005;Aganchich et al, 2009). Levels of the protective antioxidant POX were 875% higher in unstressed (100% FTSW) leaves of Z. nummularia than C. citriodora (Fig.…”
Section: Discussionmentioning
confidence: 93%